THE IMPACT OF HEALTHCARE PROVIDER BIAS ON PATIENT CARE - Mustafa Mohammad Reda Kadhim Almirza; Alshehri, Ali Abdulrahman A; Zainab Nuri A Alghirash; Al Khalefah,Ali Hussain A; Al Ghasham, Abdulkhaleq Mousa N; Alaithan, Fatimah Mohammed A; Basmah Ali Aoun Alsayafi; Al Lowimi, Jawad Hussain Jawad; Ali Ahmed Alali; Jassem Ibrahim Al Hassan; Ali Salman Ahmed Al Omaishi; Amnah Nuri Algharash; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Healthcare provider bias is a critical issue that significantly influences the quality of patient care and outcomes. This review article examines the various forms of bias exhibited by healthcare providers, such as racial, gender, and socioeconomic biases, and their impact on patient care. The review synthesizes current research findings on the prevalence of bias in healthcare settings, its effects on patient-provider interactions, treatment decisions, and health disparities. Furthermore, it explores the underlying factors contributing to healthcare provider bias, including implicit biases, stereotypes, and institutional practices. Strategies to mitigate bias and promote equitable care delivery are also discussed, including cultural competency training, diversity initiatives, and policy interventions. Understanding and addressing healthcare provider bias is essential for improving patient outcomes, reducing disparities, and fostering a more inclusive healthcare system.